A Taller‐Than‐Wide Shape Is a Good Predictor of Papillary Thyroid Carcinoma in Small Solid Nodules. (1st January 2015) - Ren, Jie; Liu, Bin; Zhang, Li-Li; Li, Hong-Yu; Zhang, Fan; Li, Shuang; Zhao, Li-Rong
Abstract : Objectives: The purpose of this study was to evaluate whether a nodule with a taller‐than‐wide shape (ie, an anteroposterior diameter that is longer than the transverse diameter on a transverse or longitudinal plane [anteroposterior‐to‐transverse ratio] >1) is a good predictor of papillary thyroid carcinoma (PTC) according to nodule size. Methods: We retrospectively examined 207 thyroid nodules in our hospital from September 2011 to February 2013. Nodules were divided into groups by size: small (≤0.5 cm; group A), medium (0.5–1 cm; group B), and large (>1 cm; group C). Sonographic features were defined as an anteroposterior‐to‐transverse ratio greater than 1, microcalcifications, blurred margins, and hypoechogenicity. Results: An anteroposterior‐to‐transverse ratio greater than 1 was the most accurate sonographic feature for predicting PTC in small nodules, with high sensitivity (81.4%) and specificity (96.8%), but it was not accurate in large nodules (>1 cm). Microcalcifications showed higher sensitivity ( P < .05) in large nodules (60.0%) than in small ones (27.9%). Hypoechogenicity and blurred margins showed high sensitivity (95.3% and 97.7%, respectively) but low specificity (19.4% and 29.9%) for diagnosis of PTC in small thyroid nodules. An anteroposterior‐to‐transverse ratio greater than 1 in conjunction with another sonographic feature achieved the highest diagnostic accuracy in small nodules. Conclusions: The predictive values of sonographic features depend on nodule size. An anteroposterior‐to‐transverse ratio greater than 1, especially in conjunction with another sonographic risk factor, showed superior performance for PTC diagnosis in small nodules.